An Investigation the Current Situation of implementing ISO 9001 Quality Management System in Construction Sector in Erbil City-Iraq - Hamadameen, Bnar Naaman; Wali, Khalil Ismail (Sulaimani Journal for Engineering Sciences, 2019)
The purpose of this study is to investigate the current situation of implementation of a quality management system (QMS) based on ISO 9001 in construction sectors (private and public) in Erbil city. This study focused particularly on main motivation for adopting ISO 9001Certification and benefits as well as obstacles facing the implementation of ISO 9001 QMS in construction private and public sector. A questionnaire has been designed for the purpose of data collection. The findings of the questionnaire indicated that the most significant motivation factors for obtaining ISO 9001Certification were to improve the company’s image and reputation, to satisfy customer requirements and expectation, to improve the quality of construction processes. While the most valuable benefits obtained from ISO 9001 Certification were improving awareness of company's objectives and policies, improves company image and reputation, and documentation and standardization of process and procedure of the projects. Whereas the major obstacles facing the implementation of ISO 9001 QMS were no existence of government regulations for mandatory implementation, lack of top management support and commitment, and inadequate employee’s culture toward quality.
Keywords: Quality Management System; ISO 9001; Erbil City